The relationship between information technology (IT) investment and firm's financial performance of public listed companies in Malaysia - Sani Stores, Fatima (2015)
Significant amounts of resources have been and continue to be invested in information technology (IT). Much of this investment is made on the basis of assumption that returns will occur. Prior studies have shown that IT investment increases firm’s performances and operational efficiency. Although, IT investment by Malaysian public listed companies (PLCs) increases annually, but the investment is still insufficient. Additionally, empirical studies and scientific research on IT and firm’s performance in Malaysian PLCs are still lacking. The objective of this research work is to examine the relationship between IT investment and firm’s financial performance in Malaysian PLCs. Firm performance was measured by revenue, return on investment (ROI) and return on assets (ROA). A panel data analysis was applied to the data observed from 2009 to 2012. Data for three years on IT investment and firm’s performance was collected from a sample of 90 firms via annual reports. The result of regressing return on investment against IT investment indicates that there is a relationship between IT investment and return on investment. However, the result of regressing return on assets and revenue indicates that there is no relationship between IT investment and return on assets, IT investment and revenue respectively. The analysis provides useful implications for managers to better understand the relationship between IT investment and firms’ performance so that they can make wiser decisions to maximize the business value of their investments.